Developing a conceptual framework to improve the implementation of 3D printing technology in the construction industry - Wu, Peng; Zhao, X.; Baller, J.; Wang, Xiangyu (EarthScan, 2018)
3D printing, as an automated construction technology, has the potential to transform the construction industry. This study attempts to propose a conceptual framework that can assist the adoption of 3D printing technology in the Australian construction industry. A total of 14 factors influencing adoption of 3D printing technology was identified from a comprehensive literature review. A questionnaire survey was performed with 105 professionals working in the Australian construction industry. ‘Building codes and regulations’, ‘top management commitment’ and ‘liability for 3D printed components’ were the top three significant factors, indicating that soft aspects of 3D printing adoption should match the technological advancement. In addition, the conceptual framework was confirmed, suggesting that technology readiness led to the effectiveness of 3D printing, organizational support, and development of policies and regulations; development of policies and regulations contributed to organizational support and effectiveness of 3D printing; and organizational support positively influences the effectiveness of 3D printing. This study for the first time proposes a conceptual framework for promoting 3D printing technology in the construction industry, thus providing an understanding of the relationships between the influential factors for both the academics and industry practitioners.